Characteristics of Chips From Scales of Carp, Tilapia and Gourami Fish Using Various Coating Flours - Decky Sapuan Ramadhani; Reza Widyasaputra; Ngatirah Ngatirah (University of Sultan Ageng Tirtayasa, 2024)
Fish scales are waste and most of them are thrown away during processing. The components of fish scales include 70% water, 27% protein, 1% fat and 2% ash. Therefore, the scales can be used as a food product in the form of chips. Fish scales can be processed into chips due to their composition of collagen that provides structural support and flexibility to the scales. The collagen fibers within the scales can be arranged and compacted to create a thin, chip-like structure that maintains its integrity and shape. Processing of fish scale chips requires flour coating. Coating can help to bind processed fish scales together, adding structural support and preventing the chips from crumbling or breaking apart during handling and consumption. This study using a randomized complete block design with two factors. The first factor is the type of fish scales, A1 (carp fish scales), A2 (tilapia fish scales) and A3 (gourami fish scales). The second factor is the type of flour, B1 (corn starch), B2 (tapioca) and B3 (rice flour). Analysis of fish scales produced included: chemical characteristics (moisture content, ash, fat, protein), physical characteristics (colour and texture), and organoleptic preference (colour, taste, aroma and texture). The results of this study indicate that variations in the types of fish scales have a significant effect on organoleptic (colour and taste), organoleptic (aromatic) significant effect. However, it did not significantly affect the moisture content, ash content, fat content, protein content, total colour difference, texture (hardness, fracture, chewiness, and cohesiveness), and organoleptic (texture). Variations in the type of flour have a significant effect on organoleptic (colour), significantly affect texture (fracture) organoleptic (taste). However, it did not significantly affect the moisture content, ash content, fat content, protein content, color, texture (hardness, chewiness, and cohesiveness), organoleptic (aromatic, and texture). The rice flour gourami scale chips and rice flour carp scale chips produced comply with SNI 8644:2018 except for the fat content. The recommended treatment is fish scale chips from gourami fish scales coated with rice flour.